PELAKSANAAN EKSEPSI SEBAGAI BENTUK PEMBELAAN DALAM PERKARA PIDANA TERHADAP DAKWAAN YANG BERTENTANGAN DENGAN PASAL 143 AYAT (2) HURUF b DIPENGADILAN NEGERI SAMARINDA - Hendra Joni Purnama (Universitas 17 Agustus 1945 Samarinda, 2013)
ABSTRACTWith the legal protection of literary, Makaterlindung also special rights which are owned by the creator of a work, especially writing. Besides, the protection to prevent piracy, and counterfeiting paper. In order to prevent copyright violations especially chapter 15 UUHC No.. 19, 2002 which is a form of law that is the basis for the establishment of business a copy of the scientific work, it is necessary to take preventive measures.